Exploring the moderating effect of emotional intelligence on the relationship between narcissism and workplace aggression - Van der Nest, Lambertus Johannes (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2010.